Effects of letrozole and clomiphene citrate on Wnt signaling pathway in endometrium of polycystic ovarian syndrome and healthy women†. Issue 3 (3rd September 2018) - Mehdinejadiani, Shayesteh; Amidi, Fardin; Mehdizadeh, Mehdi; Barati, Mahmood; Pazhohan, Azar; Alyasin, Ashraf; Mehdinejadiani, Kobra; Sobhani, Aligholi
ABSTRACT: Polycystic ovary syndrome (PCOS) is an endocrine disorder in women of reproductive age. In addition to anovulation, endometrial dysfunction can reduce fertility in PCOS. The cyclical changes of endometrium are controlled by estrogen and progesterone via modulating the Wnt/B-catenin pathway. Clomiphene citrate (CC) and letrozole are used to induce ovulation; unlike letrozole, there is a discrepancy between ovulation and pregnancy rates in CC-treated cycles. Because of the anti-estrogenic effects of CC on endometrium, we compared the expression of the key molecules of the Wnt/B-catenin pathway in the endometrium of women taking CC and letrozole. This study included PCOS and healthy women divided into the groups stimulated with letrozole (5 mg) or CC (100 mg) as well as NO-treatment groups. The endometrial thickness and hormonal profile were measured on day 12 of the menses. Using real-time polymerase chain reaction and western blot, we evaluated mRNA and protein expression of B-catenin, glycogen synthase kinase 3 beta (GSK3B), dickkopf Wnt signaling pathway inhibitor 1 (DKK1), and estrogen receptor 1 (ESR1) in the endometrial samples. Significantly, the mean serum estrogen and progesterone were lower and higher, respectively, in letrozole than CC groups. The endometrial thickness was significantly reduced in CC. The proteins expression of active B-catenin, inactive GSK3B, and ESR1 were significantly decreased in CC-treated groups. The mRNA and protein assessment of DKK1 showed significantly higher expression in CC. Our results indicate that letrozole can provide an acceptable activation of the Wnt/B-catenin pathway, resulting in adequate proliferation of endometrium in the women receiving letrozole compared to CC. Abstract : The expression of B-catenin, GSK3B, DKK1, and ESR1 were adversely affected in the endometrium of women induced with clomiphene citrate compared to letrozole, resulting in inefficacity of endometrium.